PENINGKATAN AKTIFITAS PETANI CENGKEH DI WILAYAH DESA TOULIMEMBET KECAMATAN KAKAS - Christian Masengi; Caroline B.D. Pakasi; Benu Olfie (Universitas Sam Ratulangi, 2015)
ABSTACT Toulimembet villages is one of the villages in the kakas sub district which consists of the total population 1045, the number houshold is 345, the member of farmer is 106 and member of fishermen is 56. Toulimembet village is the center of producing cloves, clove plant is an annual plant that produces Plantations harvest only four years, but did not close kemiungkinan annually cloves can also be harvested once a year. Toulimembet village besides having a mountainous area also has the advantage of the territorial waters of the lake Tondano Farmers clove well as fish farmers spend 66% per month for the initial activities for a month in September. Clove farmers at the same time fish farmers spend 66% per month during the maintenance period is from October to June. And 72% for harvesting activities conducted during one month of the month of August. Increased activity cngkeh farmers who used to cultivate only cloves just use a bit of time in the garden, with pemnafaatan territorial waters, clove farmers began adding businesses freshwater fish nets step system resulting in increased economic aktiftas. Keywords: activities and cost